Association Between Celiac Disease, Autoimmune Thyroid Disease, and Growth Failure in Paediatric Patients - Waseem Abbas, Abdul Raheem, Ali Hussain, Rana Taseer Ahmad, Anum Fatima, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Celiac disease (CD) and autoimmune thyroid disease (AITD) are frequent autoimmune disorders in paediatrics that are often associated with growth disturbances. The sooner these conditions are detected, the better, because the growth retardation and developmental delay due to late diagnosis can be severe. Objective: This study was to assess the growth failure rate in children with CD and AITD and to examine the relationship between AITD and growth parameters in children with CD. Methods: This cross-sectional study was conducted in the paediatric medicine department of Mayo Hospital Lahore from June 2022 to January 2023, including 250 children, 2–16 years old, with CD, AITD or both. Anthropometric measurements such as height, weight and BMI were taken and analysed according to WHO growth standards to calculate growth percentiles and z-scores. Laboratory laboratory tests were serological markers for CD (anti-tTG IgA) and thyroid function tests (TSH, free T4). Chronic diseases that interfered with growth were not included. To investigate the correlation between autoimmune diseases and growth failure, statistical analysis was used and chi-square tests applied to assess whether there was significance. Results: Twenty-eight percent of patients with CD had significant growth failure whereas 32 percent of those with AITD had growth deficits. Children with both CD and AITD (n=35) had a higher prevalence of growth impairment than those with one autoimmune disorder (p<0.01). There was a good correspondence between the level of growth failure and the delayed diagnosis. Conclusion: Growth failure is a risk in CD patients, particularly in those with both CD and AITD. Early diagnosis and treatment of autoimmune conditions is important in preventing growth retardation and developmental sequelae. Keywords: Celiac disease, Autoimmune thyroid disease, Growth failure, Paediatrics, WHO growth standards, Height-for-age, Serology, Endocrine disorders